Fire performance of heritage and contemporary timber encapsulation materials. (May 2020) - Chorlton, Bronwyn; Gales, John
Abstract: Cultural heritage buildings are often recognized for holding significant heritage value; however, too often these structures are lost to fire. Timber is a building material commonly found in cultural heritage buildings, and for centuries encapsulations have been used in an attempt to improve the fire performance of timber. This research examines the history and evolution of encapsulating timber to improve its fire performance, through analysis of archival literature dating to over 200 years ago, as well as by, for the first time, evaluating the fire performance of bench scale samples of these historic and reproduced encapsulations with controlled and repeatable fire testing. The purpose of the tests is to truly understand successes and failures of these protective measures and to assist architects and engineers who may encounter these dated protective coating measures on timber. Plasters, metal plates, lime-based paints, and gypsum boards were all tested using a Cone Calorimeter apparatus, following an adaptive ASTM E1354 procedure. Heat release, material decomposition, charring, and ignition of timber were all analysed. Results show that plasters and gypsum board performed similarly, although historic plasters did not stay attached to the wood substrate post-testing, making them impractical for building applications. The iron plate still allowed heat transfer into the timber, provoking measurable char depth. Finally, the lime-based paint delayed timber ignition by only 20 s. These results indicate that none of the historic encapsulations significantly improved fire performance, and they therefore cannot be relied upon for fire protection if they are found in a heritage structure. While such encapsulations may still need to be left in-place from a heritage conservation perspective, other passive and active strategies might need to be implemented into the structure to ensure its fire performance and enable its successful conservation. Highlights: Historical literary review of first controlled fire tests, obtained for the first time to be analysed providing a foundational reference . Technique for replication of these historic timber coatings using historical literature. Contemporary fire testing of these heritage coating materials to provide a subsequent ranking. All heritage coatings lacked in fire resistance when compared to modern gypsums to be relied upon in contemporary codes for fire resistance.